Experimental investigation on improvement of latent heat and thermal conductivity of shape-stable phase-change materials using modified fly ash. (10th February 2020) - Qiu, Feng; Song, Shaokun; Li, Denian; Liu, Yang; Wang, Yuqi; Dong, Lijie
Abstract: Fly ash (FA) is the solid waste discharged from thermal power plants and has become one of the largest industrial solid wastes produced annually. Meanwhile, as energy shortages and environmental pollution caused by the excessive use of fossil energy becoming increasingly prominent, an improvement in energy efficiencies and the exploitation of clean renewable energies is urgently required. In this research, we proposed to modify FA by a simple alkali treatment. The modified fly ash (mFA) exhibited an optimized multistage three-dimensional hollow morphology with abundant granules and pores on the microsphere surface. The specific surface area of the FA was 2.68 m 2 /g, while it increased to 10.32 m 2 /g for mFA. Meanwhile, the Al2 O3 content of mFA increased from 31.26 to 38.7 wt%, whereas the SiO2 content decreased from 57.43 to 44.89 wt%. After lauric acid (LA) impregnated into mFA, the shape-stable phase-change material (SSPCM) exhibited simultaneously enhanced latent heat and thermal conductivity. The latent heat and thermal conductivity of the obtained LA/mFA SSPCM was 65.7 J/g and 0.52 W/mK, which was 51.7% and 67.7% higher than that of LA/FA SSPCM, respectively. The latent heat enhancement was attributed to the larger specific surface area and the richer pore structure provided by the mFA. The significant thermal conductivity improvement was ascribed to the higher relative content of Al2 O3 and the smaller thermal resistance of LA/mFA SSPCM. Moreover, the LA/mFA SSPCM exhibited robust thermal, chemical, and morphological stability with respect to 1000 times thermal cycling. Considering the suitable phase-change temperature, high energy storage density, enhanced thermal conductivity, robust thermal reliability, applicable thermoregulatory capacity, low cost and easy processing, and role of environmental governance, the mFA based SSPCM may have widespread application in solar-energy storage, building air-conditioning system and geothermal energy utilization. Graphical abstract: Fly ash (FA) is modified using a simple alkali treatment. The modified FA (mFA) exhibits an optimized multistage three-dimensional hollow structure, providing larger specific surface area and higher void volume. Then, a novel shape-stable phase-change material (SSPCM) with simultaneously improved high latent heat and thermal conductivity is obtained by incorporating lauric acid (LA) into the mFA via a simple vacuum impregnation method. The LA/mFA SSPCM has widespread application in solar-energy storage, building air-conditioning system and geothermal energy utilization. Image 1034 Highlights: Alkali modified FA exhibits optimized multistage three-dimensional void structure. A novel SSPCM based on mFA was prepared using vacuum impregnation method. The latent heat and thermal conductivity is 63.7 J/g and 0.52 W/mK, respectively. Latent heat and thermal conductivity of LA/mFA SSPCM increases by 51.7% and 67.7%. The SSPCM has great potential in environment governance and thermal energy storage.